Lawrence v Fen Tigers: Controversies and clarifications in the law of nuisance - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2015)
The law of nuisance is an area which is fraught with difficulties. In Lawrence v Fen Tigers [2014] 2 WLR 433, the UK Supreme Court dealt with several of these issues, in particular the relevance of planning permission and when damages should be granted in lieu of an injunction. This comment examines the decision and its implications.